Pengembangan Bahan Ajar Membaca Permulaan Berbasis Kartu Huruf Untuk Siswa Kelas 1 Sekolah Dasar - Yuniarti Wulandari; Feniareny Feniareny; Rury Rizhardi; Mega Prasrihamni (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This development research aims to produce teaching materials for reading the beginning of the letters of the alphabet, vowels, and. The method used is research and development. The subjects were grade I elementary school students, totaling 20 people. Teaching materials developed using the ADDIE model, namely: (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data collection using questionnaires and tests. The data analysis technique was carried out with validity analysis, practicality analysis and effectiveness analysis. The results of data analysis are categorized as valid with an average value of 89.64%, teaching materials are categorized as practical in a one to one trial with an average value of 91.3%, small group trials with an average value of 90.7% and teaching materials are categorized as effective with an average score of 84%. Based on the validation results, practicality results, and effectiveness results, it is concluded that this textbook is suitable for use in learning Indonesian..